Mobile information and communication technologies, flexible work organization and labor productivity: Firm-level evidence - Steffen Viete; Daniel Erdsiek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Mobile information and communication technologies (ICT) have started to diffuse rapidly in the business sector. This study tests for the complementarity between the use of mobile ICT and organizational practices providing workplace flexibility. We hypothesize that mobile ICT can create value if organizational practices grant employees appropriate autonomy over when, where and how to perform work-related tasks. Our data set comprises 1132 German service firms and provides information on the share of employees that have been equipped with mobile devices which allow for wireless internet access, such as notebooks, tablets and smartphones. Workplace flexibility is measured in terms of firms' use of working from home arrangements, working time accounts, and trust-based working time. Within a production function framework, we find that the use of mobile ICT is associated with a productivity premium only in firms granting workplace flexibility by means of trust-based working time. Robustness checks suggest that our results are not driven by ICT-skill complementarity or by complementarity of mobile ICT with multiple alternative modern management practices.
Keywords: D22; L22; O33; 330